2021
DOI: 10.1186/s40824-021-00203-z
|View full text |Cite
|
Sign up to set email alerts
|

Bioceramic hydroxyapatite-based scaffold with a porous structure using honeycomb as a natural polymeric Porogen for bone tissue engineering

Abstract: Background The application of bioceramic hydroxyapatite (HA) derived from materials high in calcium to tissue engineering has been of concern, namely scaffold. Scaffold pores allow for cell mobility metabolic processes, and delivery of oxygen and nutrients by blood vessel. Thus, pore architecture affects cell seeding efficiency, cell viability, migration, morphology, cell proliferation, cell differentiation, angiogenesis, mechanical strength of scaffolds, and, eventually, bone formation. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 34 publications
2
63
0
1
Order By: Relevance
“…A successful synthesis of HA based on abalone mussel shells with a molar ratio of Ca/P of 1.67 was presented. Overall the cell metabolic activity and morphology of the HA + HCB 30 wt.% scaffolds showed that they were able to facilitate attachment of MC3T3E1 cells on their surface [ 35 ]. Porous scaffolds were fabricated with PCL/β-tricalcium phosphate (BTCP at 10, 20, and 50 wt.%) biocomposites by a freeze-drying method.…”
Section: Introductionmentioning
confidence: 99%
“…A successful synthesis of HA based on abalone mussel shells with a molar ratio of Ca/P of 1.67 was presented. Overall the cell metabolic activity and morphology of the HA + HCB 30 wt.% scaffolds showed that they were able to facilitate attachment of MC3T3E1 cells on their surface [ 35 ]. Porous scaffolds were fabricated with PCL/β-tricalcium phosphate (BTCP at 10, 20, and 50 wt.%) biocomposites by a freeze-drying method.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallographic properties of the gel HA-Abalone were determined by XRD (PAN analytical Type X'Pert Pro, Tokyo, Japan). The XRD data were recorded in the range of 2θ: 10-80° using Cu-Kα radiation at λ=0.154 nm 27) .…”
Section: Crystallographic Analysismentioning
confidence: 99%
“…The solution was then stirred at a temperature of 60ºC at a velocity of 350 rpm until it turned into a homogeneous solution. It was sonicated at a temperature of 60ºC for 1 h before the gel HA-Abalone solution was stored in the refrigerator 27,28) .…”
Section: Cell Viability Assay Of the Gel Ha-abalone 1) Extraction Solution Of Gel Ha-abalonementioning
confidence: 99%
See 1 more Smart Citation
“…One of the most crucial issues of CPCs is the control of the setting responses after chemical reaction and rheological properties to reach appropriate injectability, setting time, and mechanical properties. The porosity and microstructure of CPCs can be altered by modifying the process conditions, such as the liquid-to-powder proportion and the size of the powder [ 70 ]. The presence of pores in the set cement is very relevant for its biological and mechanical performance.…”
Section: Chemically Consolidated Calcium Phosphates As 3d Injectable Scaffoldsmentioning
confidence: 99%